CASH HOLDINGS AND FINANCIAL PERFORMANCE COMPANIES IN THE BASIC AND CHEMICAL INDUSTRY IN THE INDONESIAN STOCK MARKET - Ekaningtyas Widiastuti; Sulistyandari (Transpublika Publisher, 2023)
The modern business landscape is characterized by dynamic interactions between various financial indicators that influence a company's financial health and performance. This study aims to investigate the impact of growth, liquidity, and profitability on capital reserves. It is an associational quantitative study that utilizes secondary data. The present research adopts an associational quantitative approach, utilizing secondary data from a five-year period spanning from 2016 to 2020. The population of interest comprises basic and chemical industrial enterprises that are publicly listed on the Indonesia Stock Exchange. The study employs a robust combination of literature review and documentation techniques to collect pertinent data, creating a comprehensive foundation for analysis. To rigorously investigate the interplay of growth, liquidity, profitability, and their connection to capital reserves, the study employs advanced panel data regression analysis. The analysis reveals that growth exerts no discernible impact on cash on hand, suggesting that while expansion may drive other financial outcomes, it does not directly affect the immediate availability of capital reserves. Conversely, liquidity emerges as a crucial determinant, exhibiting a positive influence on cash on hand. This underscores the importance of maintaining a robust liquidity position, which enables companies to effectively manage day-to-day financial obligations and seize strategic opportunities. Furthermore, the study establishes a positive correlation between profitability and cash on hand. Companies that exhibit higher profitability are more likely to accumulate substantial capital reserves, reflecting a capacity to generate surplus funds even after accounting for operational expenses.